Role of Conspectus in Collection Management and Resource Sharing - Sridhar, M. S. (Journal of Information and Knowledge, 1997)
Conspectus is an instrument, an assessment methodology and a consortial database which enable providing optimum patron specific access model for resource sharing among libraries. It helps making more informed decisions regarding acquisitions, collection development, fund allocations, budget requests, grants and preservation. A systematic 'conspectus' provides many indirect benefits like (i) filling-in gaps in the collection, (ii) justifying use of approval plans identifying subject areas where curricular changes dictate that the library starts or stops buying materials, (iii) justifying a grant application or budget increase for training, preservation or collection development, (iv) defining possibilities for increased cooperative acquisitions among local or regional libraries in subject areas of mutual interest, (v) fulfilling institutional or state mandated assessment programs, (vi) providing 'objective evidence' for accredition and professional association reports, (vii) defining collection development objectives, policies, procedures and short and long range goals. The paper provides a birds-eye-view of conspectus methodology, its role in collection development, collection evaluation and resource sharing as well as some problems and pitfalls in adoption of conspectus methodology. Lastly, concludes by emphasising the need for awareness about conspectus methodology among local professionals and some sincere attempts to create such access tools rather than satisfying with acronyms of library network.